Security-constrained unit commitment model considering frequency and voltage stabilities with multiresource participation - Zidong, Zhou; Jinquan, Zhao (Frontiers in Energy Research, 2024)
The rapid increase in the proportion of renewable energy sources has led to a reduction in the relative share of synchronous units, which has resulted in a decline in the inertia of the power system and a decrease in its voltage support capacity. This has given rise to a number of issues related to the frequency and voltage stability of the power system. In order to ensure the system's frequency and voltage stability, it is necessary to maintain a number of synchronous units online in the day-ahead generation schedule. Firstly, the dynamic frequency change process after power system faults is discussed, a linear expression for the frequency stability constraints involving energy storages and wind turbines is derived. Secondly, the bus short-circuit capacity is characterized to describe the strength of voltage support, the minimum short-circuit capacity requirement of the bus is solved based on the transient voltage recovery problem after the clearance of short-circuit faults. The total short-circuit capacity provided by the unit to the bus is calculated through the network reactance matrix, the voltage stability constraint is established. Subsequently, the security-constrained unit commitment model considering frequency and voltage stability(FVS-SCUC) is established. Finally, the effectiveness of the proposed model is demonstrated through numerical simulation of the IEEE-39 system with storage and wind turbines. The model can ensure the frequency and voltage security of the system, and the renewable energy output can be improved after considering energy storage.After considering the frequency regulation effect of energy storage and wind turbine, as well as the voltage regulation effect of energy storage, the overall system cost has been reduced by nearly 30%.